Sistem Kontrol Suhu Ruangan dan Penyiraman Tanaman Bawang Merah pada Greenhouse dengan Smartphone - Aziz Musthafa; Shoffin Nahwa Utama; Triana Harmini (MULTITEK INDONESIA, 2018)
The problems faced in the agricultural sector are very huge, from the availability of land, energy, seasonal changes, pest, to crop failure. The development of modern technology is expected to help overcome some of the problems that occur. In this study will integrate microcontroller technology in agriculture. The research method starts from the stage of making greenhouses starting with designing images of smart greenhouse models. Then the stage of making a greenhouse frame from wood, for the manufacture of plant shelf frames using iron, assembling electric power generating components, making automatic control systems on the greenhouse, making formulas on Arduino Uno, testing the temperature and humidity in the greenhouse, making the plant rack manipulator on the smart  greenhouse. The short-term goal of this control system is expected to help the performance of farmers  or greenhouse management officers in controlling the watering of the crops they plant in the greenhouse, so that one day the manager does not have to always go to the greenhouse when they want to water the plants or check soil moisture.The trial was carried out for 30 days with soil temperature and humidity parameters The result, when the air temperature in the greenhouse is more than 32 C, the fan will turn on. The fan causes hot air to come out. when the temperature reaches 25 C the fan will turn off. Then when the soil moisture value on the LCD shows 17.11%, the water pump will turn on. Water from the pump is flowed to the plant media to keep the soil moist. when the value of soil moisture exceeds 70.31%, the water pump will automatically turn off. From this result, the system can be applied in building integrated farming systems and smart greenhouses.